PENGARUH TIPE NHT BERBANTUAN MEDIA AUDIO VISUAL TERHADAP HASIL BELAJAR PKn KELAS V SD - yarso, Maisaroh; Marli, Suhardi; Halidjah, Siti (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aimd to analyze the effect of using the number head together type with audio visual media on student learning outcomes in learning citizenship education 5th grade students of  public elementary 10 school in east pontianak. The method used was the experimental method, the form of research used was quasi experimental design with the design of nonequivalent control group design. The population and sample in this study were all 5th grade students of  Public Elementary 10School in East Pontianak. The data collection tool was a multiple choice test with 40 questions. Based on data analysis, the average post-test results of the experimental class were 67.03 while the average post-test results of the control class 58.36. The results of the t test obtained tcount of 2,2446 and ttable α = 5% (with dk = 35 + 35 - 2 = 68) is 1,9973, which means  tcount (2,2446)> ttable (1,9973), then Ha is accepted. It was concluded that there is a  effect of using the number head together type with audio visual media on student learning outcomes in learning citizenship education 5th grade students of  public elementary 10 school in east pontianak. From the results of ES calculations, obtained ES for 0.57 (medium criteria). This means using the number head together type with audio visual media give a good effect on student learning outcomes in learning citizenship education 5th grade students of  public elementary 10 school in east Pontianak..Keywords: Number Head Together, Audio Visual Media, Learning Outcomes